Brightly Luminescent and Color-Tunable CsPbBr3 Nanocrystals with Enhanced Stability and Room Temperature Cubic Structure through Codoping with MnCl2 - Darwish, Elshaimaa; Elia, Jack; Fehn, Dominik; Köllner, David; Pourjafar, Amir; Christiansen, Silke; Meyer, Karsten; Webber, Kyle Grant; Brabec, Christoph; Batentschuk, Miroslaw; Osvet, Andres (Advanced Engineering Materials, 2024)
Lead halide perovskites have attracted much attention from the scientific community in recent years due to their attractive properties and their proven potential in many applications. Nevertheless, their stability and lead toxicity have remained a problem. Herein, the potential of manganese as a divalent dopant to offer better stability and replace a fraction of the toxic lead ions is investigated. Moreover, the reverse microemulsion method is used to obtain tunability in emission and bandgap by doping cesium lead bromide. Furthermore, cubic cesium lead bromide particles are managed to obtain at room temperature as a result of doping.
CRIS-Team Scopus Importer:2024-05-24
Keywords: light conversion; perovskite nanoparticle; semiconductor quantum dots